Upaya Transnational Advocacy Networks dalam Mendorong Legalisasi LGBT Rights di Thailand - Tyas, Intan Kinanthi Damarin (Universitas Muhammadiyah Yogyakarta, 2019)
This paper discusses discrimination and criminalization of LGBT community due to the government change in Thailand, from absolute to constitutional monarchy. This shift caused changes in the social construction of Thai society, which led to the repression of values and norms in Buddhist beliefs whose culture of tolerance with LGBT people. This condition led the movement of Transnational Advocacy Network to promote equality and justice for LGBT through the legality of LGBT Rights. Therefore, this paper wants to identify and analyze how Transnational Advocacy Network on LGBT issues in Thailand can encourage the legality of LGBT and why this issue can be accepted within Thai society. This case analyzed by using boomerang pattern approach on Transnational Advocacy Network in Thailand. Through this network, the non-government actor in Thailand has made various efforts to encourage LGBT people to achieve equality and urged the Thai government to implement LGBT Rights legality policy through the issuance of gender equality act BE 2558 in 2015. The domestic cultural values concept used in this paper also showed that Thai people started to accept the existence of LGBT community because the values and norms of Buddhist beliefs are in fact, goes hand in hand with the LGBT Rights policy in Thailand. This could mean that values and norms of Buddhist teachings about LGBT which used to be repressed can reappear in the community.